Effect of Different concentration of the Aqueous leaf extract of Moringa olifeira on seed germination and early growth of Lycopersicon esculentum mill - ساسية محمد بن رمضان; مها عبد العال الصابري (African Journal of Advanced Pure and Applied Sciences, 2025)
Moringa is a natural source rich in bioactive compounds that have been widely studied for their potential to enhance seed germination and early plant growth. This study aimed to evaluate the effect of soaking tomato seeds (Lycopersicon esculentum Mill.) in different concentrations of aqueous moringa leaf extract (5%, 15%, 30%, and 60%), in addition to the control treatment (0% distilled water), for soaking periods of 4 and 8 hours, on seed germination and early seedling development. The statistical results showed that soaking tomato seeds for 4 hours in 5% extract significantly increased germination parameters—germination percentage, germination rate, and germination index—by 153.2%, 45.2%, and 202.5%, respectively, compared to the control. At 8 hours, the increases were 4.9%, 21.9%, and 40.9%, respectively. Regarding seedling growth, root length increased by about 63.42% at both soaking periods, while shoot length was also markedly enhanced. The 15% concentration produced a comparable stimulatory effect to the 5% treatment, particularly on germination and growth. No significant differences were observed between the soaking times for germination, whereas significant effects were found for root and shoot growth at 15% concentration across the two soaking periods. In general ,all concentrations enhanced germination and growth indicators, but the 5% and 15% treatments were the most effective compared with the control, while the 30% concentration showed the least stimulatory effect. Based on these findings, the study recommends soaking tomato seeds in 5% moringa leaf extract for either 4 or 8 hours before planting to promote germination and ensure